Screening of copy number variants in the 22q11.2 region of congenital heart disease patients from the Sao Miguel Island, Azores, revealed the second patient with a triplication - Pires, Renato (2014)
Background The rearrangements in the 22q11.2 chromosomal region, responsible for the 22q11.2 deletion and microduplication syndromes, are frequently associated with congenital heart disease (CHD). The present work aimed to identify the genetic basis of CHD in 87 patients from the São Miguel Island, Azores, through the detection of copy number variants (CNVs) in the 22q11.2 region. These structural variants were searched using multiplex ligation-dependent probe amplification (MLPA). In patients with CNVs, we additionally performed fluorescent in situ hybridization (FISH) for the assessment of the exact number of 22q11.2 copies among each chromosome, and array comparative genomic hybridization (array-CGH) for the determination of the exact length of CNVs. Results We found that four patients (4.6%; A to D) carried CNVs. Patients A and D, both affected with a ventricular septal defect, carried a de novo 2.5 Mb deletion of the 22q11.2 region, which was probably originated by inter-chromosomal (inter-chromatid) non-allelic homologous recombination (NAHR) events in the regions containing low-copy repeats (LCRs). Patient C, with an atrial septal defect, carried a de novo 2.5 Mb duplication of 22q11.2 region, which could have been probably generated during gametogenesis by NAHR or by unequal crossing-over; additionally, this patient presented a benign 288 Kb duplication, which included the TOP3B gene inherited from her healthy mother. Finally, patient B showed a 3 Mb triplication associated with dysmorphic facial features, cognitive deficit and heart defects, a clinical feature not reported in the only case described so far in the literature. The evaluation of patient B’s parents revealed a 2.5 Mb duplication in her father, suggesting a paternal inheritance with an extra copy. Conclusions This report allowed the identification of rare deletion and microduplication syndromes in Azorean CHD patients. Moreover, we report the second patient with a 22q11.2 triplication, and we suggest that patients with triplications of chromosome 22q11.2, although they share some characteristic features with the deletion and microduplication syndromes, present a more severe phenotype probably due to the major dosage of implicated genes.